Principles of genome analysis A Guide to mapping and sequencing DNA from different organisms - Primrose, S B (Blackwell Science, 1995)
The aim of this successful text is to provide a general overview of the methodology and rationale employed in this fast moving field. Topics include the organisation and structure of genomes, and sequencing methods and strategies.